Kompetensi Komunikasi Tutor Dalam Meningkatkan Kepercayaan Diri Peserta Didik - Dina Novika (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
Communication play an important role in all aspects of life, because it gives the the contribution of large in the process of attention was given to disseminating a message in the form of information and knowledge especially in helping them to education. How is it possible provide us with information communication with nothing to do, fuel price hike worried investors the communication in the world education is teachers as the communicators the and participants primary school students as communicant. A tutor which has fixed and firm the competence of a communication that good will to be able to draw sympathy school tuition than right now to heed, understand, and for the remembrance of a message on the great commission nor information to in this matter is the subject matter. Aim of this study is under way to find out the competence of communication a tutor in improving the a belief in themselves school tuition at the Yayasan Pemimpin Anak Bangsa. A theory that used in this research is a theory constructivism, the theory is well explain how ability or very works of their hands sunday prologue an individual in communications. The study used a qualitative approach was adopted with the methods observation, the objective of the interview, and documentation. The results of the research showed it was personal communication tutor at the Yayasan Pemimpin Anak Bangsa has been good enough, was seen from ability tutor use verbal communication and nonverbal messages and subject matter that is easily understood by students, a tutor who are providing support, motivation and spirit to learn back.